Effect of Clotting Time Before Centrifugation on Total Cholesterol: A Cross-Sectional Study - Fontianus Nong Melky; Nuril Sofiantin; Marisca Jenice Sanaky (Edukasi Ilmiah Indonesia, 2026)
Introduction: Pre-analytical variables are a major source of laboratory testing error, with clotting time before centrifugation representing a potentially critical factor in serum-based biochemical analysis. Although total cholesterol is considered a relatively stable analyte, minor operational variations in clotting time may affect measurement accuracy. This study aimed to determine whether differences in clotting time (30 minutes versus 60 minutes) before centrifugation affect total cholesterol results under controlled laboratory conditions. Research Methodology: A quantitative analytic study with a paired cross-sectional design was conducted in a clinical chemistry laboratory from June to August 2025. Eighteen adult participants were recruited using purposive sampling. For each participant, venous blood samples were divided into two conditions: clotting for 30 minutes and 60 minutes before centrifugation. Total serum cholesterol was measured using the enzymatic CHOD-PAP method. Data were analyzed using descriptive statistics and a Paired Sample T-Test with α = 0.05. Results: The mean total cholesterol level after 30 minutes of clotting was 141.92 ± 18.45 mg/dL, compared to 146.33 ± 19.12 mg/dL after 60 minutes. The mean difference was 4.41 mg/dL (3.10%). Statistical analysis showed no significant difference in clotting duration between the two groups (p = 0.179). Conclusion: Extending clotting time from 30 to 60 minutes before centrifugation does not significantly affect total cholesterol measurement. These findings support analytical stability within this interval and may inform evidence-based refinement of pre-analytical laboratory procedures.